Spektrum Sindrom Stevens–Johnson dan Nekrolisis Epidermal Toksik: Tinjauan Patogenesis, Diagnosis, dan Tatalaksana - Intan Wuri Handayani; Lusiana Lusiana; Hadi Firmansyah (Pusat riset dan Inovasi Nasional, 2026)
Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, life-threatening mucocutaneous reactions characterized by extensive epidermal necrolysis and mucosal involvement. The entities represent a clinical continuum distinguished by the extent of epidermal detachment (SJS <10% body surface area [BSA], SJS/TEN overlap 10–30%, TEN >30%). Most cases are drug-induced, making early culprit-drug withdrawal and structured supportive care the cornerstones of management. Immunopathogenesis is primarily mediated by drug-specific cytotoxic T cells and NK cells through granulysin, Fas–Fas ligand, and perforin/granzyme pathways, with emerging roles of necroptosis and candidate biomarkers such as RIP3 and galectin-7. Diagnosis relies on timely recognition of the characteristic painful erythematous/targetoid lesions, Nikolsky/Asboe–Hansen signs, multi-site mucositis, accurate BSA assessment, and early severity scoring (e.g., SCORTEN) to guide referral and monitoring. Systemic immunomodulators (corticosteroids, cyclosporine, IVIg, anti-TNF agents) have variable evidence; thus, individualized selection and early multidisciplinary care particularly ophthalmologic involvement are essential to reduce acute mortality and long-term sequelae.